Notes on historiography of photographs from India - Roychoudhuri, Ranu (History compass, 2023)
Despite its long and layered histories, critical analyses of photography in India began rather late and remain comparatively limited in number. However, the burgeoining scholarship in the field illuminates photography's role in conditioning modern South Asian experiences, while also highlighting the global character of the medium that complicate the unmarked history of photography. Three intertwined historiographical threads are influential in narrating the colonial Indian camera cultures. The first thread emphasized descriptive histories, the second thread debated cultural essentialism, while the third thread inquired into myriad photographic genres to rethink colonialism. An inquiry into these three threads helps reflect on the intellectual scope of photographs from colonial India, while also directing to future archival and analytical possibilities.